Bulgaria - Poverty implications of the global financial crisis - World Bank (World Bank, 2012)
There are visible signs that the global financial crisis is affecting economic growth and poverty reduction in Bulgaria. After a period of strong economic growth through 2008, Gross Domestic Product (GDP) in 2009 is projected to shrink by 3.5 percent due to the crisis, with important implications for poverty. The note identifies the following channels as having particular relevance for poverty in Bulgaria: (i) the labor market and (ii) foreign remittances. Due primarily to its effect on trade and investment, the global financial crisis could affect household welfare through contraction in the labor market and slowdown in wage growth. Remittances from abroad, which are significant contributor to consumption of nearly 7 percent of the Bulgarian households, are likely to slow down in 2009. The note estimates the potential impact on poverty of the crisis. The poverty impact is projected by simulating the effects of the anticipated slowdown in growth and remittances on household consumption using data from the 2007 Multitopic Household Survey (MTHS) and macro and sectoral growth and employment projections. Given uncertainties regarding the scale of the crisis and how households are likely to cope, the note is intended to provide indicative estimates of the poverty impact of the crisis, rather than precise estimates.